Optimalkan Pertumbuhan Ekonomi: Peran Vital Konsultan Keuangan - Afnivena Meishella; Sudiyanto Sudiyanto (Pusat Riset dan Inovasi Nasional, 2024)
The growth of many taxable entrepreneurs (PKP) is proof of good economic growth for a country. However, sometimes many entrepreneurs do not know the procedures for paying taxes, the amount of tax that must be paid, which requires them to consult a financial consultant. The increasing number of entrepreneurs in Indonesia is a new face in the economic sector, which indicates that the economy is getting better. Unfortunately, this is not comparable to their knowledge of calculating the amount of tax that must be paid. Based on this, financial consultants have a big role to play in helping those who are still confused about the amount of tax that must be paid.